2004
DOI: 10.1116/1.1676417
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical properties of sputtered vanadium oxide films

Abstract: Electrical and optical properties of sputtered amorphous vanadium oxide thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…The best fit allows to find n C = 2.3 + 0.2i in the semiconductor phase, and n H = 3.6 + 3.2i in the metallic phase (corresponding to the minimum error respectively of 1.5% and 0.5%). Although n C might seem a low value for vanadium dioxide, it is rather consistent with the wide range of values found in literature where VO 2 optical constants exhibit strong differences depending on the deposition technique, 20,[63][64][65][66][67][68][69][70][71] the substrate temperatures 63 and the oxygen pressure 64 employed during the deposition process. Once all the optical properties are found, then IR reflectance, transmittance and emissivity of any VO 2 /sapphire structure can be easily simulated and optimized as a function of VO 2 film thickness.…”
Section: Sample S1supporting
confidence: 87%
“…The best fit allows to find n C = 2.3 + 0.2i in the semiconductor phase, and n H = 3.6 + 3.2i in the metallic phase (corresponding to the minimum error respectively of 1.5% and 0.5%). Although n C might seem a low value for vanadium dioxide, it is rather consistent with the wide range of values found in literature where VO 2 optical constants exhibit strong differences depending on the deposition technique, 20,[63][64][65][66][67][68][69][70][71] the substrate temperatures 63 and the oxygen pressure 64 employed during the deposition process. Once all the optical properties are found, then IR reflectance, transmittance and emissivity of any VO 2 /sapphire structure can be easily simulated and optimized as a function of VO 2 film thickness.…”
Section: Sample S1supporting
confidence: 87%
“…(a) First, we calculated the average optical constants of vanadium dioxide, far from the SMT, in both the semiconductor state (at 30 • C), and in the metallic state (at 90 • C) by the simultaneous fit of the transmittance (T r ) and the front and rear reflectances (R f , and R r ), assuming that the silicon refractive index is n Si = 3.43, Although this method is rather inaccurate to retrieve the refractive index for nanolayers, with respect to ellipsometry, the best fit values found for the semiconductor phase (n S + ik S = 2.7 + i0.04), and for the metallic phase (n M + ik M = 2.9 + i4.8) are in agreement with the wide range of values reported in the literature for (2 µm to 3 µm) [19][20][21][22][23][24][25][26] depending on the different fabrication process (for rf sputtering Tazawa et al [24] found n M + ik M = 2.8 + i4.4). It is worth noting that our values were retrieved without using any effective medium approximation to simulate the surface roughness or [22,27].…”
Section: Optical Characterizationsupporting
confidence: 86%
“…We claim that the heterogeneity required to achieve a balance between positive and negative stiffness phases might be obtainable using microlithography or nanolithography, as described in [20]. Alternatively, one can manufacture a film containing nano-grain inclusions of phase transforming material, such as VO 2 , through sputtering deposition [21] or pulsed laser deposition [22].…”
Section: Resultsmentioning
confidence: 98%